New insights upon the reproductive biology of the sea cucumber Holothuria tubulosa (Echinodermata, Holothuroidea) in the Mediterranean: Implications for management and domestication - Pasquini, Viviana; Porcu, Cristina; Marongiu, Martina Francesca; Follesa, Maria Cristina; Giglioli, Ambra Angelica; Addis, Pierantonio (Frontiers in Marine Science, 2022)
Holothuria tubulosa is one of the most common sea cucumber species inhabiting the Mediterranean Sea. Due to its commercial interest for the international market, it has been harvested without proper management causing the overexploitation of its stocks. Inadequate management is also caused by lack of information on basic biology and ecology not allowing the estimating of the species vulnerability and resilience to growing anthropogenic pressures. In this paper, we have investigated basic life-history traits of H. tubulosa (population structure and reproductive cycle) in a population of Central-Western Mediterranean (Sardinia, Italy). A macroscopic maturity scale for both sexes was defined through an instrumental colorimetric analysis of the gonads and the ramification level of the gonad’s tubules, subsequently confirmed by histological analysis. The seasonal trend of the Gonado-Somatic Index, the changes in color of the gonads and tubules ramification indicated that the spawning period of H. tubulosa was concentrated in summer with a peak in late August, closely related to the increase in water temperature. A synchronous development of the gonads, with a unique and short reproductive event during the year, was also detected. In conclusion, this study provides new evidence on the biological and ecological features of H. tubulosa, essential data for developing a scientifically-based stock assessment as well as conservative management at a local scale. Finally, we provided basic information for the domestication of broodstock in a conservative hatchery.